Aspects of reproductive biology of curimba Prochilodus lacustris (Pisces, Prochilodontidae) in a tropical lake in Northeastern Brazil - Cardoso, Rayssa de Lima [UNESP]; Silva, Marcelo Henrique Lopes; Carvalho-Neta, Raimunda Nonata Fortes; Castro, Antonio Carlos Leal de; Ferreira, Cássia Fernanda Chagas; Ferreira, Helen Roberta Silva; Santos, Débora Martins Silva (Hindawi, 2019)
This study evaluated the annual cycle of biological reproductive aspects of Prochilodus lacustris, a neotropical fish species, in Baixada Maranhense Protection Area in northeastern Brazil. Fish were collected monthly between June of 2015 and June of 2016 using gill nets. In the laboratory, 600 individuals were weighed, measured, and eviscerated to obtain biometric data and data for the microscopic and macroscopic analyses of the maturation stages of the gonads. These analyses allowed the determination of the reproductive period using biological indicators such as the gonadosomatic index and hepatosomatic index, condition factor, stomach repletion index, and spawning season. Abiotic variables were measured in situ during the samplig: temperature, pH, dissolved oxygen, and electrical conductivity. In addition, local rainfall data was also obtained. The results showed that the total body length of individuals varied from 151 to 211 mm in males, and from 142 to 239 mm in females. The sex ratio showed a predominance of females over males, and the species showed negative allometric growth. The annual variation of reproductive indicators and the frequency of individuals in advanced stages of gonadal maturation suggest that the reproductive cycle of the species occurs between November and January, with a reproductive peak in January. This reproductive peak coincides with the beginning of the region's rainy season. Although we did not do the fertility analysis, our results suggest that the species presents partitioned spawning. In conclusion, this results demonstrates that the reproduction of the investigated specie is influenced by associations between environmental variables on a seasonal scale and can be contribute to improve the understanding of the dynamics of the physiological reproductive process in lentic environments.
Keywords: Environmental Protection Area; lentic environment; neotropical fish; reproduction